Актуальний стан та напрями розвитку системи соціального захисту людей з інвалідністю в Україні - Гіркова, Діана Іванівна; Hirkova, Diana Ivanivna (Національний університет "Львівська політехніка", 2024)
У сучасних умовах соціально-політичних трансформацій, спричинених як внутрішніми реформами, так і зовнішніми викликами, зокрема збройною агресією Російської Федерації проти України, проблема ефективного функціонування системи соціального захисту осіб з інвалідністю набуває особливої ваги. Об’єктом дослідження є система соціального захисту осіб з інвалідністю в Україні. Предметом дослідження є особливості та умови функціонування соціального захисту людей з інвалідністю, зокрема в умовах сучасних соціально-політичних трансформацій та децентралізації, а також практичні аспекти надання соціальних послуг зазначеній категорії осіб у громадах. Метою дослідження є комплексний аналіз сучасного стану, викликів та перспектив розвитку системи соціального захисту осіб з інвалідністю в Україні в умовах соціально-політичних трансформацій, зокрема децентралізації та війни, а також розробка практичних рекомендацій щодо удосконалення механізмів надання соціальних послуг на місцевому рівні. Результати дослідження: Досліджено поняття «соціального захисту», «соціальної вразливості», «дискримінації», проаналізовано концептуальні підходи дослідження особливостей системи соціального захисту людей з інвалідністю в України, визначено проблеми та потреби цільової групи, а також вивчено нормативно-правові аспекти регулювання досліджуваного процесу. Представлено науково-практичний аналіз стану системи соціального захисту людей з інвалідністю в Україні, зокрема порівняно український та зарубіжний досвід та окреслено виклики та перспективи першого. Подано результати емпіричного дослідження функціонування системи соціального захисту людей з інвалідністю в Україні на прикладі Шегинівської громади, завдяки чому виявлено основні проблеми об’єкта дослідження, подано рекомендації щодо їх вирішення.

In the current conditions of socio-political transformations caused by both internal reforms and external challenges, in particular the armed aggression of the Russian Federation against Ukraine, the problem of the effective functioning of the social protection system for people with disabilities is gaining the particular importance. The object of the study is the system of social protection of people with disabilities in Ukraine. The subject of the study is the features and conditions of functioning of social people’s protection with disabilities, in particular in the context of modern socio-political transformations and decentralization, as well as practical aspects of providing social services to this category of people in communities. The purpose of the study is a comprehensive analysis of the current condition, challenges and prospects for the development of the social protection system for people with disabilities in Ukraine in the context of socio-political transformations, in particular decentralization and war, as well as the development of practical recommendations for improving mechanisms for providing social services at the local level. Research results: The concepts of "social protection", "social vulnerability", "discrimination" were studied. Conceptual approaches to studying the features of the social protection system for people with disabilities in Ukraine were analyzed. The problems and needs of the target group were identified, and the regulatory and legal aspects of regulating the process under study were searched.A scientific and practical analysis of the condition of the social protection system for people with disabilities in Ukraine is presented, in particular, a comparative analysis of Ukrainian and foreign experience is provided, and the challenges and prospects of the former are outlined.The results of an empirical study of the functioning the social protection system for people with disabilities in Ukraine using the example of the Shegynivka community are presented, which revealed the main problems of the object of research and provided recommendations for their solution. Key words: social protection, disability, inclusion, decentralization, vulnerable group, social policy. List of used sources: Goncharov, A. (2009). The concept of social protection. Social Security Law, (10), 126–129. Zozulya, I. (2021). The concept of "social protection" in the context of scientific research. Current problems of public administration, (3(84)), 24–29. Pidlipna, R. P. (2015). To the issue of forming state policy in the sphere of social protection of the population. Scientific Bulletin of Mukachevo State University. Series: Economics, (2(4), part 2), 35–40.
Current state and directions of development of the social protection system for people with disabilities in Ukraine
Keywords: 6.232.00.00; соціальний захист; інвалідність; інклюзивність; децентралізація; вразлива група; соціальна політика